Answer:
Step-by-step explanation:
We shall apply Doppler's effect of sound .
speaker is the source , Jason is the observer . Source is moving at 10 m /s , observer is moving at 6 m/s .
apparent frequency =
![f_o*(V+v_o)/( V-v_s)](https://img.qammunity.org/2022/formulas/physics/college/skrxwi627rnwzzl9tzncchp9vffu6zgge2.png)
V is velocity of sound , v₀ is velocity of observer and v_s is velocity of source and f_o is real frequency of source .
Here V = 340 m/s , v₀ is 6 m/s , v_s is 10 m/s . f_o = f
apparent frequency =
![f* (340+6)/(340-10)](https://img.qammunity.org/2022/formulas/physics/college/4ze0ptzmrkll0wlhcchvt9ymz67fhkxin1.png)
=
![f* (346)/(330)](https://img.qammunity.org/2022/formulas/physics/college/q9d9ketavttl39vsyojnj2f9h8gek2cfvb.png)
So m = 346 , n = 330 .